2022
DOI: 10.1021/acschemneuro.1c00760
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Binding Mechanisms for Allosteric Sodium Ion in Cannabinoid Receptors

Abstract: The therapeutic potential of cannabinoid receptors is not fully explored due to psychoactive side effects and lack of selectivity associated with orthosteric ligands. Allosteric modulators have the potential to become selective therapeutics for cannabinoid receptors. Biochemical experiments have shown the effects of the allosteric Na+ binding on cannabinoid receptor activity. However, the Na+ coordination site and binding pathway are still unknown. Here, we perform molecular dynamic simulations to explore Na+ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…Docking studies reveal stable docked poses for partial agonists in both the binding pockets. In the antagonist-binding pose, we observed that the partial agonists extend downward toward Na + -binding site similar to THC ( 13 ). These partial agonists bind with similar affinity in agonist and antagonist-binding pocket.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Docking studies reveal stable docked poses for partial agonists in both the binding pockets. In the antagonist-binding pose, we observed that the partial agonists extend downward toward Na + -binding site similar to THC ( 13 ). These partial agonists bind with similar affinity in agonist and antagonist-binding pocket.…”
Section: Discussionmentioning
confidence: 92%
“…However, THC alkyl chain (side chain) orientation varies between the two binding poses. In antagonist-like pose 1, it extends toward the conserved sodium-binding site ( 13 , 26 , 27 ) similar to the arm 1 of antagonist, whereas, in antagonist-like pose 2, it orients itself in the direction of agonist-binding site similar to the arm 2 of the antagonist ( Fig. 3 , C and D ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The unbiased MD simulations suggest a sodium-binding site located in the extracellular domain of the CB 1 receptor Additionally to the detailed description of the ligand binding determinants and the receptor's structural consequence, our simulations also identified a sodium-binding site located in the Frontiers in Pharmacology frontiersin.org extracellular side. Previously, the location of a binding-site at the TM domain of the CB 1 receptor has been identified (Dutta et al, 2022b;Katritch et al, 2014). From our unbiased MD simulations and in both CB 1 complexes, we observed the formation of this extracellular sodium-binding site formed by residues located in the extracellular segment of TM5 and TM6, and the extracellular loop 2.…”
Section: 5mentioning
confidence: 99%